The complexity of hispanic religious life in the 16th-18th centuries - Moreno, Doris, (Cuneiform Monographs;, 2020)
In The Complexity of Hispanic Religious Life in the 16th-18th Centuries, Doris Moreno has assembled a team of leading scholars to discuss and analyze the diversity of Hispanic religious and cultural life in the Early Modern Age. Using primary sources to look beyond the Spanish Black Legend and present new perspectives, this book explores the realities of a changing and plural Catholicism through the lens of crucial topics such as the Society of Jesus, the Inquisition, the Martyrdom, the feminine visions and conversion medicine. This volume will be an essential resource to all those with an interest in the knowledge of multiple expressions of tolerance and cultural dialectic between Spain and the Americas.